The Economic Crisis and the Reshaping of Geography - Oßenbrügge, Jürgen (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
An exploration of roots and effects of the recent economic and fiscal crisis reveals temporal and spatial characteristics which are used in this paper in order to discuss concepts and explanations from Economic Geography. In general, we may observe a transformation of Western economy and society which, labeled as financialisation, has increasingly structured spatial development on different scales recently. The paper explores (a) more systematically when, where and to what extent geographical elements accelerate crisis developments. These arguments build on the theoretical explanation brought forward by David Harvey and the French regulation school. These insights form (b) a background for arguments for an economic geography of “glocal” crisis in order to improve our explanatory abilities. Strong geographical components become obvious in the causes of the subprime crisis – an issue which reflects the ways the built environment is organised. Furthermore, effects of the crisis reinforce processes of uneven development on both international and sub-national scales.